2009
DOI: 10.1186/1747-1028-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Chk1

Abstract: Chk1 is a serine/threonine protein kinase that is the effector of the G2 DNA damage checkpoint. Chk1 homologs have a highly conserved N-terminal kinase domain, and a less conserved Cterminal regulatory domain of ~200 residues. In response to a variety of genomic lesions, a number of proteins collaborate to activate Chk1, which in turn ensures that the mitotic cyclin-dependent kinase Cdc2 remains in an inactive state until DNA repair is completed. Chk1 activation requires the phosphorylation of residues in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 46 publications
2
62
0
1
Order By: Relevance
“…Despite recognition of the importance of S345/S317 phosphorylation, it remains unclear how this phosphorylation activates Chk1 (28)(29)(30). We showed that Chk1-S expression did not change appreciably in DDR (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Despite recognition of the importance of S345/S317 phosphorylation, it remains unclear how this phosphorylation activates Chk1 (28)(29)(30). We showed that Chk1-S expression did not change appreciably in DDR (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Earlier work suggested that the C-terminal domain may antagonize the N-terminal kinase domain via an intramolecular interaction that can be disrupted by phosphorylation, leading to Chk1 activation (31). This "autoinhibition" model, although supported by some observations (28), has been seriously challenged (30). Alternatively, Chk1 activity may be governed by a repressing factor(s), the dissociation of which from Chk1 leads to Chk1 activation (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chk1 kinase has a basal activity level which increases ,5-10 fold upon phosphorylation of S345 in its Cterminal domain (Capasso et al, 2002;Kosoy and O'Connell, 2008). The details of its activation remain to be resolved, but it is generally believed that modification of S345 by ATR Rad3 releases the C-terminal domain from the N-terminal catalytic domain thereby stimulating kinase activity (Tapia-Alveal et al, 2009). DNA damage-induced phosphorylation at S345 is removed by Dis2 phosphatase in S. pombe (den Elzen and O'Connell, 2004) and by protein phosphatase 2A (PP2A) in human cells (LeungPineda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, while deletion of the regulatory domain increases Chk1 activity in vitro (Chen et al 2000), it is essential for Chk1 function in vivo (Kosoy and O'Connell 2008). Further, mutations in the C-terminal domain can either inactivate or super-activate Chk1 function in vivo (Wang and Dunphy 2000;Kosoy and O'Connell 2008;Palermo et al 2008;Pereira et al 2009), suggesting that it contributes more than an inhibitory function to the catalytic domain (Tapia-Alveal et al 2009). …”
mentioning
confidence: 99%